Genome-wide approach to study gene–nutrient intake interactions in type 2 diabetes mellitus in a large Korean cohort - Park, Jae-Min; Choi, Ja-Eun; Song, Youhyun; Kwon, Yu-Jin; Lee, Ji-Won; Hong, Kyung-Won (Frontiers in Nutrition, 2025)
IntroductionA comprehensive understanding of gene–diet interactions is necessary to establish proper dietary guidelines for the prevention and management of type 2 diabetes mellitus (T2DM). We examined the roles of genetic variants and their interactions with T2DM-associated nutrients in a large-scale genome-wide association study of Korean adults.MethodsA total of 50,808 participants from a Korean genome and epidemiology study were included. Dietary intake was assessed using a food frequency questionnaire. Dietary nutrient intake was classified based on the Korean Dietary Reference Intakes (DRIs). Odds ratio (OR) and 95% confidence interval were calculated after adjusting for age, sex, exercise, smoking, alcohol consumption, total energy consumption, principal component 1, and principal component 2.ResultsAmong the individuals consuming vitamin A (retinol equivalent) above the DRI, the carriers of the melanotransferrin (MELTF) rs73893755 minor allele (T) had a higher risk of T2DM than the non-carriers (OR = 1.85, p-value = 1.66 × 10−8; interaction p-value = 7.61 × 10−8). Similarly, among the individuals consuming cholesterol (mg/day) above the DRI, the carriers of the tripartite motif-containing protein 25 (TRIM25) rs139560285 minor allele (A) had a higher risk of T2DM than the non-carriers (OR = 2.02, p-value = 4.06 × 10−8; interaction p-value = 4.28 × 10−8).DiscussionOur results suggest that interactions between specific polymorphisms and certain nutrients may influence T2DM development.